2018
DOI: 10.1039/c8cp02151a
|View full text |Cite
|
Sign up to set email alerts
|

Fermi resonance in solvated H3O+: a counter-intuitive trend confirmed via a joint experimental and theoretical investigation

Abstract: The spectral features of H3O+ between 3000 and 3800 cm-1 are known to be dominated by coupling between the fundamentals of stretching modes and the overtones of bending modes. A strong Fermi resonance (FR) pattern has been observed in Ar-tagged H3O+, and the sensitive dependence of the FR pattern on the number of Ar tags has been analyzed by Li et al. [J. Phys. Chem. A, 2015, 119(44), 10887]. Based on ab initio anharmonic calculations with MP2/aug-cc-pvDZ, Tan et al. investigated the influence of different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 51 publications
5
55
0
Order By: Relevance
“…It is obvious that it decreases from 136 cm −1 in TMA‐H + …Ar to 104 cm −1 in TMA‐H + …EtOH. A similar trend has been found in our previous work on H 3 O + solvated in rare gas; in those systems, the coupling strength between fundamental of the O‐H + stretching and overtone of the bending modes decreases as the strength of hydrogen bonding increases (which is correlated with the decrease of the frequency of the stretching mode) [26] . While this tendency is seen in both solvated H 3 O + and TMA‐H + …X, the coupling strength in TMA‐H + is two to three times greater than its counterparts in H 3 O + .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It is obvious that it decreases from 136 cm −1 in TMA‐H + …Ar to 104 cm −1 in TMA‐H + …EtOH. A similar trend has been found in our previous work on H 3 O + solvated in rare gas; in those systems, the coupling strength between fundamental of the O‐H + stretching and overtone of the bending modes decreases as the strength of hydrogen bonding increases (which is correlated with the decrease of the frequency of the stretching mode) [26] . While this tendency is seen in both solvated H 3 O + and TMA‐H + …X, the coupling strength in TMA‐H + is two to three times greater than its counterparts in H 3 O + .…”
Section: Resultssupporting
confidence: 88%
“…The current version of our ab initio anharmonic algorithm is based on the Discrete Variable Representation (DVR) method [23, 24] . Details of the implementation of our Gauss‐Hermite DVR programs have been described in the previous papers on the FR in micro‐solvated H 3 O + [25, 26] . In the previous works, we found that CCSD offers a substantial improvement over MP2 in predicting frequencies of proton stretching modes; we also found seven grid points for the bending and stretching modes of micro‐solvated H 3 O + are sufficient to reduce the uncertainty of eigenvalues to be less than 2 cm −1 .…”
Section: Resultsmentioning
confidence: 87%
“…A similar situation has been observed in the vibrational spectra of symmetric and antisymmetric free OH modes of H 3 O + ⋯N 2 and H 3 O + ⋯Ar. 34 To support our arguments, we simulated the rotational profiles of ν 3free and ν 3HB using PGOPHER 35 at different rotational temperatures. The resulting spectra are shown in Supporting Information Figure S9.…”
mentioning
confidence: 81%
“…[23,24] Details of the implementation of our Gauss-Hermite DVRprograms have been described in the previous papers on the FR in micro-solvated H 3 O + . [25,26] In the previous works,wefound that CCSD offers asubstantial improvement over MP2 in predicting frequencies of proton stretching modes;w ea lso found seven grid points for the bending and stretching modes of micro-solvated H 3 O + are sufficient to reduce the uncertainty of eigenvalues to be less than 2cm À1 . Thanks to the reduced dimensionality and rapid convergence of Gauss-Hermite quadrature (seven grid points for each mode), both the PES and dipole moment surface (DMS) of TMA-H + …X are computed directly at CCSD/aug-cc-pVDZ in the present case for better accuracy.…”
Section: Theoretical and Computational Analysismentioning
confidence: 87%
“…As imilar trend has been found in our previous work on H 3 O + solvated in rare gas;i n those systems,the coupling strength between fundamental of the O-H + stretching and overtone of the bending modes decreases as the strength of hydrogen bonding increases (which is correlated with the decrease of the frequency of the stretching mode). [26] While this tendencyi ss een in both solvated H 3 O + and TMA-H + …X, the coupling strength in TMA-H + is two to three times greater than its counterparts in…”
Section: Analysis Using Matrix Elementsmentioning
confidence: 98%